Implementation and Research of Finite Element Method for Nonlocal Elasticity Theory Problems in Julia Programming Language - Kuvyrkin, G.N.; Savelyeva, I.Y.; Sokolov, A.A.; Cherednichenko, A.V.; Novozhilova, O.V. (2023 Applied Mathematics, Computational Science and Mechanics: Current Problems (AMCSM), 2023)
The article proposes an implementation option for a finite element software package written in the Julia programming language that solves three-dimensional nonlocal elasticity theory problems. The article discusses the main features of the nonlocal theory and the implementation algorithm, taking into account the Julia language features. A number of calculations and comparisons of classical and nonlocal theories are carried out on the example of the problem of applying a load to the rigidly fixed beam end.